Association of type and location of BRCA1 and BRCA2 mutations with risk of breast and ovarian cancer - Rebbeck, Timothy R.; Mitra, Nandita; Wan, Fei; Sinilnikova, Olga M.; Healey, Sue; Mcguffog, Lesley; Mazoyer, Sylvie; Chenevix-Trench, Georgia; Easton, Douglas F.; Antoniou, Antonis C.; Nathanson, Katherine L.; et al. (Journal of the American Medical Association, 2015)
Importance: Limited information about the relationship between specific mutations in BRCA1 or BRCA2 (BRCA1/2) and cancer risk exists. Objective: To identify mutation-specific cancer risks for carriers of BRCA1/2. Design, Setting, and Participants: Observational study ofwomen whowere ascertained between 1937 and 2011 (median, 1999) and found to carry disease-associated BRCA1 or BRCA2 mutations. The international sample comprised 19 581 carriers of BRCA1 mutations and 11 900 carriers of BRCA2 mutations from 55 centers in 33 countries on 6 continents.We estimated hazard ratios for breast and ovarian cancer based on mutation type, function, and nucleotide position.We also estimated RHR, the ratio of breast vs ovarian cancer hazard ratios. A value of RHR greater than 1 indicated elevated breast cancer risk; a value of RHR less than 1 indicated elevated ovarian cancer risk. Exposures: Mutations of BRCA1 or BRCA2. Main Outcomes and Measures: Breast and ovarian cancer risks. Results: Among BRCA1 mutation carriers, 9052 women (46%) were diagnosed with breast cancer, 2317 (12%) with ovarian cancer, 1041 (5%) with breast and ovarian cancer, and 7171 (37%) without cancer. Among BRCA2 mutation carriers, 6180 women (52%) were diagnosed with breast cancer, 682 (6%) with ovarian cancer, 272 (2%) with breast and ovarian cancer, and 4766 (40%) without cancer. In BRCA1, we identified 3 breast cancer cluster regions (BCCRs) located at c.179 to c.505 (BCCR1; RHR = 1.46; 95%CI, 1.22-1.74; P = 2 × 10-6), c.4328 to c.4945 (BCCR2; RHR = 1.34; 95%CI, 1.01-1.78; P = .04), and c. 5261 to c.5563 (BCCR2', RHR = 1.38; 95%CI, 1.22-1.55; P = 6 × 10-9).We also identified an ovarian cancer cluster region (OCCR) from c.1380 to c.4062 (approximately exon 11) with RHR = 0.62 (95%CI, 0.56-0.70; P = 9 × 10-17). In BRCA2, we observed multiple BCCRs spanning c.1 to c.596 (BCCR1; RHR = 1.71; 95%CI, 1.06-2.78; P = .03), c.772 to c.1806 (BCCR1'; RHR = 1.63; 95%CI, 1.10-2.40; P = .01), and c.7394 to c.8904 (BCCR2; RHR = 2.31; 95%CI, 1.69-3.16; P = .00002).We also identified 3 OCCRs: the first (OCCR1) spanned c.3249 to c.5681 that was adjacent to c.5946delT (6174delT; RHR = 0.51; 95%CI, 0.44-0.60; P = 6 × 10-17). The second OCCR spanned c.6645 to c.7471 (OCCR2; RHR = 0.57; 95%CI, 0.41-0.80; P = .001). Mutations conferring nonsense-mediated decay were associated with differential breast or ovarian cancer risks and an earlier age of breast cancer diagnosis for both BRCA1 and BRCA2 mutation carriers. Conclusions and Relevance: Breast and ovarian cancer risks varied by type and location of BRCA1/2 mutations. With appropriate validation, these data may have implications for risk assessment and cancer prevention decision making for carriers of BRCA1 and BRCA2 mutations.
CRIS-Team Scopus Importer:2022-11-17